Assessing the precision of machine tools through various measurement systems - Tešić, Saša; Jotić, Goran; Čiča, Đorđe; Sredanović, Branislav; Štrbac, Branko; Ranisavljev, Miloš (Journal of Production Engineering, 2023)
Nowadays, machine tools have to meet high precision requirements when it comes to manufacturing parts that have to correspond exactly to the specified geometries. Achieving high precision and accuracy when machining parts is a growing challenge, especially as machine tool operating hours increase. This increasing challenge emphasizes the need for regular verification of machine tool accuracy. In this study, the accuracy of a three-axis milling center was investigated, analyzing different measurement systems suitable for evaluating the precision of machine tools. The main objective was to evaluate the feasibility of using faster and less expensive inspection methods and measurement systems without compromising the reliability of the evaluation process. The research included an investigation of two different measurement systems developed for the acquisition of machine tool accuracy data: a coordinate measuring machine equipped with a contact sensor and a 3D laser scanner. The aim of this comparative analysis is to identify optimal approaches to machine tool accuracy assessment that balance speed and affordability while ensuring the reliability and trustworthiness of the test results obtained.